FACTORS INFLUENCING CONSUMERS’ ONLINE PURCHASE INTENTION OF APPAREL ON SOCIAL COMMERCE MEDIATED BY TRUST - Ahmad, Siti Nor Bayaah; Juprie, Debra Jacyntha (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME'S (AIJBES), 2025)
This study explores the factors influencing consumers' online purchase intention of apparel on social commerce platforms, with a particular focus on the mediating role of trust. The research examines the impact of perceived usefulness, perceived ease of use, perceived risk, and electronic word-of-mouth (e-WOM) on online purchase intention. Data was collected through an online questionnaire distributed via Google Forms, yielding 165 valid responses. The data was analyzed using Microsoft Excel and SmartPLS 4. The findings reveal that both perceived usefulness and perceived ease of use significantly and positively influence trust in the social commerce environment. Trust, in turn, is shown to have a significant positive relationship with online purchase intention of apparel. Furthermore, the study confirms that trust mediates the relationship between perceived usefulness and online purchase intention, as well as the relationship between perceived ease of use and online purchase intention. These insights contribute to a better understanding of how trust functions as a crucial mediator in the decision-making process of consumers in social commerce, offering valuable implications for marketers and platform designers aiming to enhance online purchase intentions.